Electrometric studies on formation of cerium vanadates as a function of pH - Prasad, Saradh; Leite, Valderi Duarte; Santana, Renato Alexandre Costa; de Medeiros, Emanuelle Araújo (Eclética Química, 2006)
The precise nature of the reaction between nitric acid and sodium ortho-vanadate solutions has been studied by means of electrometric techniques involving potentiometric and conductometric titrations. The well defined inflections and breaks in the titration curves confirm the existence of the anions, pyro-V 2 O 74- , meta-VO 3- and poly-H 2 V 10 O 284- corresponding to the ratios of VO 43- :H + as 1:1, 1:2 and 1:2.6 in the neighborhood of pH 10.5, 7.4 and 3.6, respectively. The interaction of cerium(III) nitrate with sodium vanadate solutions, at specific pH levels 12.4, 10.5, 7.4 and 3.6 was also studied by potentiometric and conductometric titrations between the reactants. The end-points obtained from the sharp inflections in the titration curves provide definite evidence for the formation and precipita- tion of cerium ortho-Ce 2 O 3 .V 2 O 5 , pyro-2Ce 2 O 3 .3V 2 O 5 and meta-Ce 2 O 3 .3V 2 O 5 vanadates in the neigh- borhood of pH 7.4, 6.2 and 4.8, respectively. Analytical investigations on the precipitates formed con- firm the results of the electrometric study.